Edukasi Gentle Birth Untuk Persalinan Nyaman Pada Kelas Ibu Hamil Di UPTD Puskesmas Tanoyan - Hamzah, Strahmawati; Saleh, Sitti Nurul Hikma; Muzayyana, Muzayyana (Journal of Excellence Humanities and Religiosity, 2026)
Maternal and infant health is one of the important indicators of the success of a country’s health system. Childbirth is the final phase of pregnancy that requires optimal physical and psychological readiness because it carries a risk of serious complications. The labor process often triggers high levels of anxiety in pregnant women. High anxiety and medical interventions during childbirth not only affect the birth experience but also contribute to the risk of maternal and neonatal complications. Gentle birth is a childbirth preparation method that emphasizes a calm, minimally traumatic process and optimizes physiological capabilities. The purpose of this community service activity was to increase pregnant women’s knowledge of gentle birth for a comfortable childbirth experience. This activity consisted of three stages: the preparation and planning stage, which included the division of tasks among the service team and a pre-test; the implementation and process stage, which included gentle birth counseling; and the monitoring and evaluation stage, which included a post-test and an overall evaluation of the activity. The community service activity was carried out well and in accordance with the plan. There was an increase in pregnant women’s knowledge of gentle birth for comfortable childbirth, with a mean difference in participants’ knowledge scores before and after the counselingof 7.27.